O ativismo judicial e seus efeitos sobre os direitos fundamentais: as implicações das ingerências do judiciário brasileiro nas garantias individuais - Farias, Débora Maria Silvestre (Universidade Federal Rural do Semi-Árido, 2018)
This article presents the theme of judicial activism and fundamental rights. Addresses the legal objectives of the division of powers and implications in the praxis of the Brazilian Supreme Court. It is justified by a notorious national feeling of dissatisfaction with the Federal Supreme Court's decisions. Methodologically it is carried out through the legal-philosophical study and analysis of decisions of the Judiciary Power, in particular, the judgment of habeas corpus nº 124,306. Reveal the conclusions of legal uncertainty and legal rupture. It proposes the conversion into Law of Law Project (PL) 4754/2016 for modification of the Law on Crimes of Liability (Law 1,079 of April 10, 1950) in order to typify usurpation of competence of the Legislative Branch or Executive Branch.
Artigo Acadêmico
Keywords: Ativismo judicial; Crime de responsabilidade; Habeas corpus; Tripartição de poderes; Aborto; Judicial review; Responsibility crime; Habeas corpus; Checks and balances; Abortion; CIENCIAS SOCIAIS APLICADAS::DIREITO